New International Efforts for Freshwater Research, Education, and Conservation: A report from the Society for Conservation Biology’s Freshwater Working Group - Kasangaki, Aventino; Hitt, Nathaniel P.; Ogada, Mordecai (My University, 2007)
Freshwater ecosystems are vital for human well-being and ecological integrity but are increasingly jeopardized by habitat loss and degradation, fragmentation, water abstraction, and climate change. These threats are diverse and pervasive and thus require new thinking about conservation problems and solutions. Here, we describe the Society for Conservation Biology’s Freshwater Working Group (FWWG) and invite ICOET members to join this initiative. First, we review the origins of the FWWG and briefly describe previous accomplishments. Second, we describe the international composition of the FWWG and current activities. Third, we propose new research questions regarding the effects of transportation networks on freshwater ecosystems. We explain that the landscape structure of freshwater ecosystems is distinct from terrestrial environments and that localized, direct effects of roads must be understood in the context of regional, indirect effects of landscape connectivity and other factors. We conclude that freshwater conservation requires new research across ecological scales and new collaborations across political boundaries
Keywords: ecosystems; Freshwater; habitat loss